Evaluation of sanky peel extract in the stability of llama meat - Contreras-López, Eliana (2020)
In this study, the stability of the sensory quality and viable mesophilic aerobic (AMV) counts of llama ground meat with the addition of sanky (Corryocactus brevistylus subsp. puquiensis (Rauh & Backeberg) Ostolaza) peel ultrasound-assisted extract (CES) was evaluated during storage at 5°C , the added extract volume was calculated to obtain a concentration of 60 mg PT / kg of llama ground meat. The instrumental parameters of color (L*, a*, b*), pH, AMV and sensory properties were determined during nine days. The samples without extract (CO) presented higher values​​ of a* (redness) than the CES samples; however, the L* (luminosity) and b* (yellowness) values ​​did not show significant differences for the CES treatment during storage. The color difference (ΔE0-9) during storage was greater for the CO treatment, indicating significant changes in color and odor that were perceived by consumers. The treatments did not show significant differences in the AMV count (p>0,05). In conclusion, the sanky peel ultrasound-assisted extract did not exhibit antimicrobial effects on llama ground meat; but it did help to maintain its color and odor during refrigerated storage.